RELEVANCE OF THE STATE DEBT POLICY OF UZBEKISTAN - Turaeva Sevara; B.I. Nurmukhamedova (KONFERENSIYALAR, 2025)
State debt policy plays a key role in ensuring macroeconomic stability and sustainable development of the economy of Uzbekistan. Public debt management is an important tool for financing the budget deficit, implementing investment programs, and supporting vulnerable segments of the population. Public debt management in Uzbekistan is based on the key principles of transparency, accountability and long-term sustainability. Modern approaches to debt structuring and servicing are used, aimed at minimizing risks and optimizing the cost of borrowing.